VALU 1994 - SVT:s vallokalsundersökning riksdagsvalet 1994 - Näsman, Per; Hernborn, Hans; Holmberg, Sören; Thedéen, Torbjörn (Swedish National Data Service, 2008)
The first Swedish exit poll survey (VALU) was carried out in connection with the elections in 1991, and it was followed by a similar survey in 1994. Voters leaving the polling stations were asked to fill in a questionnaire including questions on: party voted for in the general and local elections; time for decision how to vote; party voted for in the general election 1991; vote intention at the referendum on Swedish EU-membership; placement on a political left-right scale; confidence in Swedish politicians; gender, age, occupational group and union membership. The respondents also had to indicate how important a number of items were for the decision how to vote, and to give an opinion on the policy of the different political parties. In VALU 1994, Sweden (constituencies) was divided into geographical regions grouped around six major university cities (Lund, Göteborg, Växjö, Stockholm, Sundsvall och Luleå). In each of the regions, a university teacher was engaged as regional survey leader. The survey leaders acted as supervisors for the field agents who carried out the survey in the polling stations and early voting stations respectively. All survey leaders had knowledge of statistical methodology. I samband med valet 1991 genomfördes den första svenska vallokalsundersökningen. Undersökningen utfördes av Sveriges Television/Sveriges Radio i samarbete med universiteten i Göteborg och Stockholm. Liknande undersökningar har sedan dess genomförts i samband med samtliga riksdagsval, folkomröstningar och val till EU-parlamentet. En vallokalsundersökning innebär i korthet att ett urval av väljare får besvara ett antal frågor då de lämnar vallokalen. Syftet med VALU är att ge ett bakgrundsmaterial för den valvaka som sänds i radio och TV direkt efter vallokalerna stängts. Med hjälp av undersökningen kan omfattande analyser av valresultatet ske redan under valvakan. VALU 1994 innehöll frågor om: vilket parti man röstat på i riksdags- respektive kommunalvalet; vilket parti man röstat på i riksdagsvalet 1991; tidpunkt då ...